El papel de las entidades de crédito en España durante los últimos cincuenta años (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
In this article the author appraises the evolution of credit institutions in Spain. These institutions have played and still play a relevant role in financing the Spanish economy. Their transformation throughout the analysis period show that the banks have needed to accommodate to the legislative avatars, to the economic and social events and eventually to different business models. At present, there exists a range of strategy possibilities that these entities must embrace in order to overcome the so needed change that will allow them to maintain their role in the Spanish economy.
Keywords: financial institutions; banks; European Central Bank; Bank of Spain; economic policy; strategy; change